Evaluation of surfactants of thyme oil microcapsules by coacervation - Martins, I.M. (2011)
The formation of microcapsules (size, shape and stability) is greatly affected by the conditions used in the o/w emulsion preparation, being particularly relevant the used surfactant. The objective of this work is to study the effect of using different surfactants with hydrophilic-lipophilic balance (HLB) values from 11 to 16.5 in the encapsulation process of thyme oil by coacervation using polylactide (PLA) with polymer wall. Different emulsions of thyme oil were prepared and the surfactants investigated were Tween® 20, Tween® 80, Tergitol™ 15-S-9 and a combination of Tergitol™ 15-S-9 with Span® 85. Microcapsules size, morphology and encapsulation efficiency were studied as a function of the used surfactant.